AN ANALYSIS CODE MIXING IN GITA SAVITRIS’S YOUTUBE VIDEO ENTITLED “CHILDFREE” - Dzurratul Afra Afifah; Elvina Muhvita Wardani; Eva Lailatus Syarifah; Evi Yuli Utami; Faisal Rahman; Faiqatul Izzah; Firdausa Widiasari; Halimatus Sa’diyah (Al-Qalam Institute, 2023)
Sociolinguistics is the study of the relationship between language and society. Every society has different language styles when they interact with each other. With the many variations they have, it allows them to mix their languages in their speech. The mixing of one language with another, in the field of sociolinguistics is called code-mixing. The use of code-mixing in society has become common. This happened to one YouTuber, Gita Savitri. Therefore, this research focuses on code mixing that appears in Atta Halilintar's YouTube channel videos. The purpose of this research is to find out the types of code mix that appear in Gita Savitri's YouTube video channel. This research uses descriptive qualitative methods and humans as the main instruments in this research. In collecting data, this research uses the documentation method. This research uses content analysis which focuses on analyzing the types of code-mixing defined by Musyken. Then, the results of the types are calculated by using Musyken's formula and Hoffman’s theory. As a result, there are 39 insertion utterances, 59 substitution utterances, 25 congruent lexicalization, 60 intra lexical code ming,73 intra sential code mixing utterances in the childfree episode.